Chemical and dynamical evolution of early-type galaxies - Scott, N; Nicholas Scott (2011)
In this work I have examined the spatially resolved properties of the local early-type galaxy population. Using Hubble Space Telescope and ground based photometry I constructed Jeans Anisotropic Multi Gaussian Expansion models of the SAURON sample of early-type galaxies, from which I determined the depth of the local gravitational potential well, quantified by the local escape velocity, Vesc. I found that Vesc correlated tightly with the three Lick indices: Mgb, Fe5015 and Hβ. The Mgb-Vesc relation within individual galaxies is identical to that between different galaxies; the relation is both local and global. The Mgb-Vesc relation is: log Mgb = (0.35 ± 0.01) log Vesc − (0.41 ± 0.03). While the metallicity, [Z/H] is correlated with Vesc it does not show the same local and global behaviour. Age (t) and alpha enhancement ([α/Fe]) are only weakly correlated with Vesc. A combination of [Z/H] and t is tightly correlated with Vesc, with scatter comparable to the Mgb-Vesc relation, and does show the local and global behaviour. This combination is given by: log Vesc = 0.85[Z/H] + 0.43 log t. Using the volume limited ATLAS3D sample of 260 local ETGs I examined in detail the behaviour of the Mgb-Vesc relation and its dependence on other galaxy properties. I found that systematic deviations from the relation correlate with the local environmental density and molecular gas mass of a galaxy, and with the local [α/Fe] measurement. I found that there is a population of galaxies that do not follow the relation, found only at Vesc < 400 kms−1 . These galaxies have negative gradients, high central Hβ indices and young (t < 3 Gyrs) ages. Using stellar population models I demonstrated that these negative gradient galaxies are perturbed from the relation by recent star formation and will return to the relation as they age. I also describe the observation, reduction and analysis of a new sample of ETGs in the core of the Coma cluster, the highest density environment in the local Universe, observed with the SWIFT Integral Field Spectrograph. I determined the fraction of slow rotators in the sample, comparing it to results from the ATLAS3D survey, and found an enhanced slow rotator fraction in the Coma cluster. I also determined the Fundamental Plane of Coma early-type galaxies, given by: log Re = (1.20 ± 0.22) log σe − (0.79 ± 0.09) log〈Ie〉.